Efficient Wideband Characterization of Low-Height RF Substrates Using a Destructive Measurement Approach - Georges Zakka El Nashef; Abdel Karim Abdel Karim; Sawsan Sadek (Eng)
This paper presents a validated, cost-effective technique for the wideband characterization of low-height substrate materials in RF circuits. The method utilizes traditional resonant structures to accurately determine essential parameters—relative permittivity and loss tangent—and delivers reliable results even in the presence of unavoidable fabrication imperfections, thereby enhancing its reliability for RF designers. While it covers a broad frequency range (8–16 GHz), the proposed technique can be adapted for other ranges by modifying the resonant structure dimensions. By combining reflection coefficient and input impedance measurements of a multimode patch antenna, substrate properties are accurately extracted using an iterative numerical fitting process, i.e., secant algorithm. This approach provides RF designers with the precise material data necessary to enhance circuit performance and is especially useful for low-height substrates. The technique’s validity is demonstrated through excellent agreement between simulations and measurements, establishing that the technique provides a practical, solution for industrial and research applications.